PENAPISAN BAKTERI ENDOFIT ASAL TANAMAN KARET DAN UJI DAYA ANTAGONISNYA TERHADAP JAMUR Rigidoporus microporusPENYEBAB PENYAKIT JAMUR AKAR PUTIH PADA TANAMAN KARET (Hevea brasiliensis Muell Arg.) - Rini Sri Putri; Fifi Puspita; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to isolate and to study the antagonicity of endophytic bacteria from rubber plant to Rigidoporus microporus Cif. and to identify the higher antagonicity isolates. The research has been conducted at Plant Pathology Laboratory, Agriculture Faculty, Universty of Riau from April until June 2017. The research used explorational method (isolation and purification of the bacteria from rubber plant), experimental method (antagonicity test of bacteria endophytic from rubber plant to Rigidoporus microporus) and observation methods (hypersensitive test and characterization of five high antagonicity isolates to Rigidoporus microporus). Data collected from step 1,3 and 4 were analyzed descriptively. Step 2 used analysis of variance. The mean treatments were compared with Duncan’s new multiple range test at 5% level. Result of the research showed that there were 9 different bacterial isolates based on their color and shape of colony. There were four highest antagonicity bacteria, i.e: isolate rod-2(56,32%), leaf-4 (48,45%), root-3 (46,11%) and leaf-3 (45,50%). The four bacteria are not hypersensitive due to the absence of the necrosis on injected tobacco leaf. The four highest antagonicty bacteria was identified as Bacillus (rod-2), Enterobacter (leaf-4), Aeromonas (root-3) and Listeria (leaf-3). Keywords:Endophytic Bacteria, Rubber Plant, AntagonicityR. mic